Parasympathetic regulation of heart rate in rats after 5/6 nephrectomy is impaired despite functionally intact cardiac vagal innervation - Kuncová, Jitka; Švíglerová, Jitka; Kummer, Wolfgang; Rajdl, Daniel; Chottová-Dvořáková, Magdalena; Tonar, Zbyněk; Nalos, Lukáš; Štengl, Milan (Nephrology, dialysis, transplantation, 2009)
BACKGROUND: Chronic renal failure is frequently associated with a high risk of sudden cardiac death due to dysfunction of the autonomic nervous system. The pathogenic mechanisms underlying the parasympathetic cardiac dysautonomia are not fully elucidated yet. METHODS: Chronic renal failure was induced in rats by 5/6 nephrectomy. Blood pressure, resting heart rate and plasma levels of creatinine, urea and asymmetric dimethylarginine (ADMA) were measured. To characterize the parasympathetic innervation of the heart, chronotropic responses to atropine, metipranolol and to vagal stimulation in the absence or presence of ADMA were investigated in vivo. In vitro, chronotropic and inotropic effects of carbachol and ADMA and mRNA expression of muscarinic M2 receptors, high affinity choline transporter (CHT1), vesicular acetylcholine transporter (VAChT) and choline acetyltransferase (ChAT) were assessed in the isolated cardiac tissues. RESULTS: In 5/6 nephrectomy rats, the resting heart rate was significantly higher and the parasympathetic tone, measured as the effect of atropine after administration of metipranolol was significantly lower than in control animals. Plasma ADMA levels were significantly elevated in the uraemic rats and significantly inversely correlated with the effect of atropine on the heart rate. No differences were revealed in the plasma norepinephrine concentrations, negative chronotropic responses to stimulation of the vagus nerves, chronotropic and inotropic responses to carbachol and the relative expression of M2 receptors, CHT1, VAChT and ChAT. CONCLUSION: The data suggest that cardioacceleration in chronic renal failure is caused by a diminished cardiac parasympathetic tone in the presence of a functionally intact intrinsic cardiac cholinergic signalling system.
Keywords: Plasma Membrane Neurotransmitter Transport Proteins; messenger RNA; Rats; Parasympatholytics; proteiny přenášející neurotransmitery přes plazmatickou membránu; nefrektomie; karbachol; Atropine; Metipranolol; mužské pohlaví; Parasympathetic Nervous System; Rats, Wistar; Vesicular Acetylcholine Transport Proteins; Heart Rate; krysa rodu Rattus; noradrenalin; Nerve Tissue Proteins; western blotting; polymerázová řetězová reakce s reverzní transkripcí; vezikulární transportní proteiny acetylcholinu; srdeční frekvence; cholin-O-acetyltransferasa; Blotting, Western; metipranolol; Nephrectomy; RNA, Messenger; zvířata; kardiotonika; parasympatolytika; nervus vagus; Choline O-Acetyltransferase; proteiny nervové tkáně; ledviny; parasympatický nervový systém; Cardiotonic Agents; atropin; Heart; Reverse Transcriptase Polymerase Chain Reaction; Carbachol; potkani Wistar; Kidney; Vagus Nerve; Norepinephrine; beta blokátory; srdce; Male; Adrenergic beta-Antagonists; Animals